Report of the Joint Select Committee on the Subject of a Lunatic and Orphan Asylum (Document (North Carolina. General Assembly), 1840)
1840 Report of the Joint Select Committee on the subject of a lunatic and orphan asylum, considering only that portion which relates to a lunatic asylum. After determining the numbers of potential sufferers, the costs and effectiveness of treatment in other asylums, the committee concluded that such an asylum for "lunatics" should be constructed. Moreover, the economics suggested that doing so would be advantageous given the alternative of using a hospital or the like.